Influence of sulphur and bio-regulators on growth, yield and oil content of cumin (Cuminum cyminum) - MEHRIYA, MOTI LAL; GEAT, NEELAM; SARITA, SARITA (The Indian Journal of Agricultural Sciences, 2022)
Sulphur and bio-regulators influence various physiological and biochemical activities inside the plant. The present study aimed to evaluate the effect of sulphur and bio-regulators (ascorbic acid, thioglycolic acid and salicylic acid) on growth, yield and essential oil content in cumin (Cuminum cyminum L.). A field experiment was conducted during rabi 2013–14, 2014–15 and 2015–16 at Agricultural Research Station, Mandor (Agriculture University, Jodhpur). Factorial randomised block design with three replications was used. Four levels of sulphur (0, 15, 30 and 45 kg/ha) and four sprays of bio-regulators (Ascorbic acid, TGA and salicylic acid) @100 ppm at vegetative and flowering stage were applied. Pooled data revealed that application of sulphur @45 kg/ha significantly increased number of branches/plant, plant height (cm), number of umbels/plant, umbelletes/umbel, seeds/umbellete, test weight and also seed yield over control. Foliar application of bio-regulators @100 ppm at vegetative and flowering stage significantly increased the seed yield and oil content of cumin. The highest net return ` 93250 and benefit: cost ratio 3.32) was observed on application of sulphur @45 kg/ha followed by thioglycolic acid (net return ` 86120/ha, B:C ratio 3.12). Thus, we can recommend the application of sulphur and TGA bioregulator to the farmers in western arid zone for doubling the farmers' income in a sustainable way.